Lifetime reproductive success and heritability in nature - Merila, J; Sheldon, B (2000)
The observation that traits closely related to fitness ('fitness traits') have lower heritabilities than traits more distantly associated with fitness has traditionally been framed in terms of Fisher's fundamental theorem of natural selection - fitness traits are expected to have low levels of additive genetic variance due to rapid fixation of alleles conferring highest fitness. Subsequent treatments have challenged this view by pointing out that high environmental and nonadditive genetic contributions to phenotypic variation may also explain the low heritability of fitness traits. Analysis of a large data set from the collared flycatcher Ficedula albicollis confirmed a previous finding that traits closely associated with fitness tend to have lower heritability. However, analysis of coefficients of additive genetic variation (CV(A)) revealed that traits closely associated with fitness had higher levels of additive genetic variation (V(A)) than traits more distantly associated with fitness. Hence, the negative relationship between a trait's association with fitness and its heritability was not due to lower levels of V(A) in fitness traits but was due to their higher residual variance. However, whether the high residual variance was mainly due to higher levels of environmental variance or due to higher levels of nonadditive genetic variance remains a challenge to be addressed by further studies. Our results are consistent with earlier suggestions that fitness-related traits may have more complex genetic architecture than traits more distantly associated with fitness.